2016
DOI: 10.1371/journal.pone.0150124
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-C Is a Thyroid Marker of Malignancy Superior to VEGF-A in the Differential Diagnostics of Thyroid Lesions

Abstract: IntroductionThyroid nodular goiter is one of the most common medical conditions affecting even over a half of adult population. The risk of malignancy is rather small but noticeable–estimated by numerous studies to be about 3–10%. The definite differentiation between benign and malignant ones is a vital issue in endocrine practice. The aim of the current study was to assess the expression of vascular endothelial growth factor A (VEGF-A) and VEGF-C on the mRNA level in FNAB washouts in case of benign and malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This increase in the expression of the VEGFA gene in goiter may be due to several factors. Increasing endothelial cells is the first step in goiter formation, which exhibits levels of VEGFA expression similar to those observed in some types of thyroid cancer [23][24][25]. It is also worth mentioning that most of the papillary cancer samples analyzed in the present study presented early stages according to the TNM (Classification of Malignant Tumors) classification and that the levels of VEGFA gene expression increased according to the types and stages of tumor [15].…”
Section: Discussionsupporting
confidence: 81%
“…This increase in the expression of the VEGFA gene in goiter may be due to several factors. Increasing endothelial cells is the first step in goiter formation, which exhibits levels of VEGFA expression similar to those observed in some types of thyroid cancer [23][24][25]. It is also worth mentioning that most of the papillary cancer samples analyzed in the present study presented early stages according to the TNM (Classification of Malignant Tumors) classification and that the levels of VEGFA gene expression increased according to the types and stages of tumor [15].…”
Section: Discussionsupporting
confidence: 81%
“…Recent results reported by Woliński et al 43 suggested that the measurement of VEGF -C mRNA levels is important to distinguish benign and malignant thyroid lesions. They concluded that VEGF -C expression on the mRNA level is more useful than VEGF -A mRNA expression.…”
Section: Figurementioning
confidence: 99%
“…High hopes have been pinned on sonoelastography and the application of artificial intelligence [5]. In addition, molecular studies have become an increasingly useful and available tool in thyroid cancer risk assessment [6,7]. In particular, we hope that the introduction of these methods will allow us to reduce the amount of invasive practices performed unnecessarily in patients with benign nodules.…”
mentioning
confidence: 99%